Utilisation of municipal fly ash : environmental and goetechnical aspects - Tan, Leong Chee. (2009)
Incineration has become one of the principal methods for municipal solid waste disposal particularly in large cities throughout the world. In Singapore, a daily average of 6000 tonnes of solid waste was collected in 1993. About 80% of them was incinerated. After incineration, the total solid waste was reduced to about 20% by weight in the forms of fly ash (MFA) and other residues. MFA consists of very fine particles entrained in incinerator exhaust gases. MFA collected from the incinerators equipped with lime-based flue gas cleaning scrubbers contains a high percentage of lime. Currently, the MFA and other residues are disposed of by landfill.